2017
DOI: 10.1016/j.jsps.2016.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cryoprotection on particle size stability and preservation of chitosan nanoparticles with and without hyaluronate or alginate coating

Abstract: The aim of the present study was to determine the effect of different cryoprotectants and their concentration on the physicochemical characteristics of chitosan nanoparticles (CS-NPs). The effect of coating of CS-NPs with hyaluronic acid (HA) and alginic acid (ALG) before and after lyophilization was also evaluated. The ionic gelation method was used for the preparation of NPs and six different types of cryoprotectants (sucrose, glucose, trehalose, mannitol, polyethylene glycol-2000, and polyethylene glycol-10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(49 citation statements)
references
References 21 publications
3
43
0
Order By: Relevance
“…Similarly, particle size of nanoliposmes varied from 145 to 161 nm, which confirmed the encapsulation of nisin inside the lipid bilayer and core. Previously, it was observed that main factors influencing the average size and zeta potential of multi-component systems were pH, Ca 2+ , ALG, and CTS concentration (Li et al, 2013 ; Almalik et al, 2017 ). Moreover it was previously observed that more than 0.2% Ca 2+ ratio in ALG solution increased the particle size (Caetano et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, particle size of nanoliposmes varied from 145 to 161 nm, which confirmed the encapsulation of nisin inside the lipid bilayer and core. Previously, it was observed that main factors influencing the average size and zeta potential of multi-component systems were pH, Ca 2+ , ALG, and CTS concentration (Li et al, 2013 ; Almalik et al, 2017 ). Moreover it was previously observed that more than 0.2% Ca 2+ ratio in ALG solution increased the particle size (Caetano et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…In this study, alginate hydrogel polymer as a natural polysaccharide derived from brown algae was used as surface coating of AuNPs. Besides improving the biocompatibility and stability of nanoparticles and aqueous solubility of drugs, alginate can extend the blood circulation life time of nanocarriers and prevents them from rapid body clearance . This in turn enhances the bioavailability of drug payloads in tumor microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…Uncoated chitosan NPs were to increase in size by storage at 25°C for 3 m in 10% glucose solution [213]. This alteration in size results in modified physicochemical, pharmacodynamic and pharmacokinetic properties of the PMNPs.…”
Section: Stability Of Npsmentioning
confidence: 99%